Combined acupuncture-medicine anesthesia used in thyroid surgery: A systematic review and meta-analysis. Issue 1 (6th January 2023) - Zhang, Wei; Zhang, Meng; Han, Yanxun; Liu, Yuchen; Liu, Yehai; Sun, Chunping
Abstract : Background: Combined acupuncture-medicine anesthesia (CAMA) is extensively used in thyroid surgery in China. We conducted a systematic review and meta-analysis to assess the efficacy and safety of CAMA. Methods: We searched the China National Knowledge Infrastructure (CNKI), VIP database, WanFang database, PubMed, EMBASE, and the Cochrane Library for relevant literature. The term of literature was published before April 18, 2020, and there were no restrictions on publication language, region, or publication year. The inclusion criteria included a randomized controlled trial (RCT) of acupuncture combined with cervical plexus anesthesia. We used RevMan5.3 software for data analysis. If the chi-square test showed no significant heterogeneity ( P > .10, I 2 < 50%), we used the fixed-effect model to calculate risk ratio (RR) and mean difference. Otherwise, the random-effects model was used. Results: Overall, 18 RCTs involving 1211 patients were included in the study. The anesthesia significant rate (ASR) in the transcutaneous electrical acupoint stimulation (TEAS) plus cervical plexus block anesthesia (CPBA) and electroacupuncture (EA) plus CPBA groups was significantly higher compared with the CPBA group (TEAS + CPBA: P < .001; EA + CPBA: P < .001). The pooled effect values of the intraoperative heart rate (HR) and mean arterial pressure (MAP) were significantly lower in both the TEAS + CPBA and EA + CPBA groups relative to the control group (HR: P = .05, P < .001; the MAP: P = .002, P < .001; respectively). Moreover, the postoperative adverse reaction was markedly lower in the experimental group than in the control group (RR = 0.30, P < .001), and there was no heterogeneity between the two groups ( P = .71, I 2 = 0%). Conclusion: Combined acupuncture-medicine anesthesia significantly increases the anesthesia significance rate, reduces the intraoperative heart rate, and blood pressure, and reduces the incidence of postoperative adverse reactions. However, more high-quality future studies should be conducted to validate the efficacy and safety of acupuncture combined anesthesia further.